High-level resistance to (-) enantiomeric 2'-deoxy-3'-thiacytidine in vitro is due to one amino acid substitution in the catalytic site of human immunodeficiency virus type 1 reverse transcriptase. - Boucher, C A (1993)
Passage of human immunodeficiency virus type 1 in the presence of increasing 2'-deoxy-3'-thiacytidine (3TC) concentrations results in high-level (> 100-fold) 3TC-resistant viruses. All 3TC-resistant viruses possess a substitution at the second codon (from a methionine into an isoleucine) at position 184 within the highly conserved motif (YMDD) of human immunodeficiency virus type 1 reverse transcriptase. 3TC-resistant viruses were cross-resistant to the (-) enantiomer of the fluorinated derivative of BCH-189 but remained susceptible to 2',3'-dideoxyinosine and 2',3'-dideoxycytidine. The susceptibilities of the 3TC-resistant viruses to the (+) enantiomers of BCH-189 and the fluorinated derivative of BCH-189 demonstrate an enantiomeric specificity for viruses selected under these conditions. Introduction of an isoleucine substitution at codon 184 into a background of two known 3'-azido-3'-deoxythymidine resistance mutations (amino acids 41 and 215) restored the susceptibility of this virus to 3'-azido-3'-deoxythymidine.